The Political Communication Movement Called ‘Emak-Emak’ of the Presidential Election in Indonesia 2019 - PRASETYOWATI, RIRIS AISHAH; Zahrotunnimah; Zahrotunnimah (Archives of Business Research, 2019)
Abstract.Political events do require political communication, either through media or direct action in the form of practical movements and activities. Even The 2019 presidential election was not missed from this actions. It can be seen that there was a political communication movement called “emak-emak” initiated by a group of women who felt that their rights were harmed by the incumbent regime. This “emak-emak” movement emerged due to political awareness and solidarity, and not by the political engineering from the opposition camp. When referring to historical experience, the appearance of such movements is a natural thing. As happened in the previous part of Europe which became the forerunner of the International Women’s Day on March 8. This study used a descriptive method of empirical analysis by collecting data from the realities that occur in the field.Keywords: Political Communication, Movement, emak-emak